If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2) + y = 12 Multiply 3 * 2 6 + y = 12 Solving 6 + y = 12 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + y = 12 + -6 Combine like terms: 6 + -6 = 0 0 + y = 12 + -6 y = 12 + -6 Combine like terms: 12 + -6 = 6 y = 6 Simplifying y = 6
| 3x/5-6=9 | | 3(6)+y=12 | | x+11=2x-1 | | -7+6(-4q+19)=20-3-19q | | 3(4)+y=12 | | 8(x-4)+9-3(x+5)+38=0 | | 29x+5=30x+1 | | 8x-7+3-x=14-4x | | 99=-3x | | 8.3u+19.72-18.2u=-19.88-14.4u | | x*x+x-42=0 | | 8x-7+3-x=14+4x | | 6f+11.89=1.9f | | -4.41-11.9k=14.38-10.4k+8.96 | | 8x-7-3-x=14+4x | | -k(x-1)+2kx=1 | | 18.7-15.1b=-17.4b-19.02 | | x/.010 | | 8x+8=17x-3 | | -7.7p=-8.5p-11.2 | | -9r+17=-14-20-12r | | -8h+18=-10h | | X=ln21/ln8 | | 3k+m=10 | | 1+2c=4c+19 | | 5-3(4-2x)+3-2(5-x)=0 | | 4/5k=5/2 | | -8t=-13+20 | | Kx-k=1 | | -18m+1=-m+20-18m | | 23x+1=22x+4 | | -14-8n=18-16n |